Immune responses following DNA vaccination by needle-free injection against Burkholderia pseudomallei hemolysin co-regulated protein 1 - Michael L. Davies; Sergei S. Biryukov; Christopher P. Klimko; Jennifer L. Dankmeyer; Nathaniel O. Rill; Melissa Hunter; Christopher T. Braun; Deven W. Patrick; Tyrique D. David; Steven A. Kwilas; Carlos I. Rodriguez; Brian A. Smith; et al. (Frontiers in Immunology)
Burkholderia pseudomallei is a facultative intracellular bacterium found in soil, which causes melioidosis, a disease with diverse symptomatology. B. pseudomallei is an emerging threat in the United States based on recent environmental samples and case reports. Acute infection is 10%–40% fatal depending on treatment conditions. No vaccines for B. pseudomallei have been approved for human use, although several are under development, mostly targeting the antigens Hcp1 (hemolysin-coregulated protein 1) and CPS (capsular polysaccharide). For development of new vaccines, DNA compares favorably to other platforms in storage stability, low cost, and ease of design. Needle-free jet injection has been effective in immunizing against several infections in laboratory animals; the delivery devices are simple to use and have been FDA 510k cleared for human use. Herein, we developed a DNA vaccine targeting Hcp1 (pWRG/Hcp1) and delivered it to rabbits and mice by jet injection using a PharmaJet Stratis and a prototype adjustable-dose PharmaJet Tropis, respectively. The Hcp1 DNA vaccine was unadjuvanted and not combined with any other B. pseudomallei antigens. Immunization was followed by assessment of serum antibodies and cellular immunity against Hcp1 protein. Rabbits and mice showed induction of anti-Hcp1 antibodies after as few as two doses of pWRG/Hcp1, and splenocytes responsive to restimulation with Hcp1 protein were also detected after two doses. These results demonstrate the feasibility of inducing immunity against Hcp1 of B. pseudomallei using DNA alone. These results also serve as a proof-of-concept for immunizing mice with a PharmaJet device previously only used for larger animals.